From Movement to Expression: Integrating Performing Arts and German Language Instruction to Enhance University Students’ Speaking Proficiency - Rahma Rahma; Muftihaturrahmah Burhamzah; Irwan Irwan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study examines the integration of movement-based arts into German language instruction to enhance students’ speaking skills. The “From Movement to Words” approach treats bodily movement as an expressive and cognitively enriching medium rather than a simple visual aid. The method fosters linguistic, emotional, and symbolic engagement by incorporating gestures, embodiment, improvisation, and dance. A qualitative design was employed through classroom observation, in-depth interviews, and reflective documentation to capture pedagogical effects and experiential dimensions of learning. Findings show that movement integration improves pronunciation, vocabulary retention, and fluency while strengthening confidence, emotional involvement, and creative expression. Students described the process as more dynamic, immersive, and meaningful than conventional instruction. The study demonstrates that movement-based teaching provides a holistic, engaging, and learner-centered approach that supports cognitive and affective development. This approach affirms the potential of embodied instruction to align language learning with the evolving demands of 21st-century education.